2014
DOI: 10.1097/rlu.0000000000000274
|View full text |Cite
|
Sign up to set email alerts
|

68Ga DOTATATE PET/CT Imaging of a Solitary Fibrous Tumor of the Nasopharynx

Abstract: Solitary fibrous tumors (SFTs) are rare group of mesenchymal tumors that occurs predominantly in the pleura. The role of PET/CT imaging in characterizing the SFT is not well reported. Mesenchymal tumors may express somatostatin receptors. We hereby report a rare case of SFT of the nasopharynx showing Ga DOTATATE avidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…Lensing et al 10 have shown 18 F-PSMA avidity within a pleural SFT in a patient with diagnosed prostate cancer. Furthermore, the avidity for 68 Ga-DOTATATE has also been demonstrated in SFTs 11,12 . In our reference case of a rare presentation of extrapulmonary SFT, 68 Ga-PSMA has shown better avidity in comparison to the 18 F-FDG imaging.…”
supporting
confidence: 55%
“…Lensing et al 10 have shown 18 F-PSMA avidity within a pleural SFT in a patient with diagnosed prostate cancer. Furthermore, the avidity for 68 Ga-DOTATATE has also been demonstrated in SFTs 11,12 . In our reference case of a rare presentation of extrapulmonary SFT, 68 Ga-PSMA has shown better avidity in comparison to the 18 F-FDG imaging.…”
supporting
confidence: 55%
“…Solitary fibrosis tumour of the nasopharynx and coexistence of pituitary macroadenoma and multiple paragangliomas were detected using [ 68 Ga]Ga‐DOTA‐TATE. The agent was found valuable in evaluation of children with opsoclonus‐myoclonus ataxia syndrome providing rapid diagnosis and staging as well as guiding patient management .…”
Section: Targeted Imagingmentioning
confidence: 99%
“…Ga-DOTATATE uptake has been frequently reported in various nonendocrine tumors and lesions resulting in interpretative errors. [7][8][9][10] According to Kagna et al, 11 the 68 Ga-DOTA-NOC uptake was not associated with any NET in 72% of cases, and the uterus was the third most common location of tracer accumulation. Furthermore, the benign uptake of DOTATATE tracer by uterine fibroid has been described in few studies, attributing to the aberrant expression of somatostatin receptors or hypermetabolism of the fibroid tissue.…”
mentioning
confidence: 99%
“…Although the 68 Ga-DOTATATE PET/CT scans are highly sensitive and specific in detecting NETs, false-positive uptake may lead to diagnostic challenges 3–6 . 68 Ga-DOTATATE uptake has been frequently reported in various nonendocrine tumors and lesions resulting in interpretative errors 7–10 . According to Kagna et al, 11 the 68 Ga-DOTA-NOC uptake was not associated with any NET in 72% of cases, and the uterus was the third most common location of tracer accumulation.…”
mentioning
confidence: 99%